VD_FINDINFO Arrêt / 2017 / 350 vom 11. Juli 2017 - VD Tribunal cantonal (2017)
DÉCISION DE COTISATIONS ARRIÉRÉES, DÉCISION ADMINISTRATIVE VICIÉE | 49 LPGA, 3 al. 1 LPA-VD, 3 al. 2 LPA-VD, 42 let. c LPA-VD